Managing the Grids of the Future in Developing Countries : Recent World Bank Support for SCADA/EMS and SCADA/DMS Systems - Nangia, Varun (World Bank, Washington, DC, 2016)
SCADA/EMS and SCADA/DMS systems ensure that power grids are efficient, resilient, and able to adapt to changes in generation, transmission, and distribution. Advancing technology is making SCADA systems more capable and enabling new monitoring and management applications. World Bank support for such systems is crucial to ensuring the sustainable long-term growth of power networks in developing countries. Meanwhile, the potential exists to significantly enhance grid management in many cases by activating already installed equipment.